RELATIONSHIP BETWEEN COMPETITION ANXIETY AND FEAR OF FAILURE AMONG SPORTSMEN AND SPORTSWOMEN - Amjad, Rabia; Irshad, Erum; Gul, Ruqaia (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the relationship between competition anxiety and fear of failure among sportsmen and sportswomen. Methodology: It was a descriptive observational study, conducted from Febru- ary 2012 to January 2013, consisting of athletes from public and private sector colleges and universities of District Peshawar, Mardan and Nowshera. Sports Competition Anxiety Test (SCAT) and Performance Fear Appraisal Inventory (PFAI) were used. T-test was used to assess the gender differences of competi- tion anxiety and fear of failure. P value <0.05 was considered significant. Results: The sample consisted of 200 athletes, 100 males and 100 females. The mean age of the sample was 22.43 ±4.82 years. The mean SCAT score in the study was 28.57 ±05.38. It was significantly higher in male athletes as compared to female (p value =.004). The mean PFAI score was 70.01 ±20.58. Male athletes showed significantly higher values as compared to their female counterparts with p value <.01. There was a strong positive correlation between competition anxiety and fear of failure with correlation values ranging from .839 to .985 and P value <.001. Conclusion: There was strong positive correlation between competition anxi- ety and fear of failure. Male athletes have higher competition anxiety and fear of failure as compared to their female counterparts.